Study of Milk Yield and Some of Its Chemical Components and Its Relationship with Lambs Growth of Awassi Sheep - Abdullah, Muthanna Fathi (Journal of agricultural, environmental and veterinary sciences, 2023)
Data were analyzed from of two flocks of Awassi sheep. The first flock belongs to the College of Agriculture and Forestry, Mosul University, and the second flock belongs to Animal Breeding Station, Mosul (Al-Rashedia) which conducted on 799 and 802 records of ewes and born lambs were recorded during two seasons 2009-2010. The results revealed highly significant (P<0.01) effects for the flock, year, age of dam, and type of birth on daily milk yield (DMY). The year had a highly significant influence (P<0.01) on all milk traits except on fat percentage. The age of dam also had a significant effect (P<0.05) on Somatic Cell Count (SCC). The effects of the flock, age of dam, type of birth and sex of lamb were highly significant (P<0.01) on birth weight (BW), weaning weight (WW), and gain from birth to weaning (GBW). The year had a significant influence (P<0.01) on (WW) and (GBW). There were Positive and highly significant (P<0.01) correlation between milk components, between milk yield and (BW), (WW), and between (BW) and (WW). While it was negative between milk yield and its components.